The economy of icons : how business manufactures meaning - Sternberg, Ernest, 1953- (Praeger, 1999)
This text examines various industries to show how business endows products with evocative meaning. The author argues that foods now appeal through their sensuality and nosalgia, that houses and stores draw customers through their exoticism, and that tourist destinations offer thematic experiences.